Enhancing Maharah Kalam: Android-Based Learning Media Development and Efficacy - Arif, Faiz Nur Ihsan; Hikmah , Khizanatul (Indonesian Journal of Islamic Studies, 2024)
In the era of advancing technology and globalization, education is significantly influenced by sophisticated technological advancements. This research aims to elucidate the process of developing Android-based learning media utilizing smart app creators and to assess its effectiveness in enhancing maharah kalam. Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) up to the Implementation stage, the study garnered favorable ratings from media experts (76% indicating 'good'), material experts (84% indicating 'very good'), and students (82% indicating 'very good'). Pre-test and post-test results revealed a notable improvement, with mean scores of 77.5000 and 82.6667 respectively, signifying a significant enhancement in students' maharah kalam proficiency. This research highlights the potential of technology-based learning media in optimizing language education outcomes. Highlight: Integration of Advanced Technology: This research addresses the significant impact of sophisticated technology on contemporary education, emphasizing the development of Android-based learning media for language proficiency enhancement. Effective Implementation through ADDIE Model: The study employs the systematic ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to ensure a comprehensive approach in creating and implementing the learning media, up to the Implementation stage. Positive Assessment from Experts and Students: The research results showcase favorable evaluations from both media experts (76% indicating 'good') and material experts (84% indicating 'very good'). Additionally, students' responses indicate a substantial improvement in their maharah kalam proficiency, emphasizing the effectiveness of the technology-based learning approach. Keyword: Technology-Based Learning Media, Android Applications, Maharah Kalam Proficiency, ADDIE Model, Language Education Optimization